Pemaknaan, Sosialisasi, dan Internalisasi Filsafat Noken dalam Komunikasi Pembangunan Masyarakat Kota Jayapura - Avelinus Lefaan (Jurnal Komunikasi, 2023)
This study aims to reveal the meaning of noken, and how the socialization and internalization of the noken philosophy in Jayapura society in the dynamics of development communication. The research method uses field studies. Data was collected through in-depth interviews. The results of the study show that the meaning of the Jayapura people for noken is not only as a work of civilization in the form of an art object in the form of a knitted bag, but also contains a philosophy regarding Papuan socio-cultural values. On the other hand, even though noken contains a philosophical meaning full of Papuan values, the people of Jayapura and Papua in general do not know the philosophical meaning of noken. This research suggests the need for communication activities aimed at socializing and internalizing the noken philosophy to the people of Jayapura. Socialization should be carried out using a positivistic paradigm communication model, while at the internalization level using a constructivist paradigm.